Study of Charged States During X-Ray Interference in Crystalline Lattices - Khan, Ziarmal Mawla; Waliullah, Qasimi; Roshan, Hairan; Khan, Ziarmal Awal (Journal for Research in Applied Sciences and Biotechnology, 2024)
The discovery of X-rays at the end of the 19th century led to a real breakthrough in the study of the structure of matter. X-rays, which belong to the group of electromagnetic waves, collide with the atoms of solid matter depending on their wavelength and energy, therefore, their three-dimensional interference occurs in the structure of a crystal lattice. When such radiation is incident on a crystal, a complex pattern of radiation is created which reflects the crystal structure. In this section, the charging of the entire crystal lattice is studied during collision with a specific atom in the crystal lattice.